The Association of Choledochal Cyst and Pancreatitis: A Case Report and Review of the Literature - Yeliz Çağan Appak; Cüneyt Günşar; Güzide Doğan; Serdar Tarhan; Erhun Kasırga (Galenos Yayinevi, 2017)
Choledochal cysts are relatively rare congenital anomalies which are characterized by dilatation of the extra-and/or intra-hepatic bile ducts. Pancreatic involvement before choledochal cyst operation might be a risk factor for postoperative pancreatitis. In this case report, we present a patient who had pancreatic enzyme elevation before choledochal cyst operation and who developed acute pancreatitis after surgery.